Self-Reliance in Disaster Recovery: A Systematic Literature Review 1990-2019. - Oloruntoba, Richard; Asare-Doku, Winifred (Jacksonville State University, 2021)
Community and governmental agencies often address disaster recovery and resilience. However, few studies focus on how to achieve self-reliance and use the psychological resources within to be adaptive and resilient in disaster recovery. This systematic literature review explores models of self-reliance in disaster recovery and resilience in order to (1) identify the range of publications on the topic in the literature, and (2) to identify the range of constituent elements that have been proposed as contributing to the idea of self-reliance and self-help as a subset of individual psychological and trait resilience in disaster recovery contexts. The systematic literature review found three elements of individual resilience in the study: faith, religious practices, and psychological capital, all of which may contribute to self-reliance and self-help as a subset of individual psychological and trait resilience in disaster recovery. The findings of this study may assist with utilizing strengths that can improve the activation of individual response and resilience in disaster recovery contexts.